A Dual-Axis Electrostatically Driven MEMS Microgripper. (24th November 2014) - Jia, Yukun; Jia, Minping; Xu, Qingsong
This paper presents the design of a new monolithic two-axis electrostatically actuated MEMS microgripper with integrated capacitive position and force sensors working at the micro-scale level. Each of the two jaws of the microgripper possesses two degrees-of-freedom (DOF) and is capable of positioning in both x-and y-axes. Unlike existing works, where one gripper arm is actuated and other one is sensed, both arms of the proposed microgripper are actuated and sensed independently. A sensing scheme is constructed to provide the position and force signals in the noncontact and contact phases, respectively. By applying a 120V driving voltage, the jaw can provide 70 μm x-axis and 18 μm y-axis displacements with the force of 190 μN. By this design, the real-time position and grasping force information can be obtained in the dual sensing mode. Both analytical calculation and finite-element analysis (FEA) were performed to verify the performance of the proposed design. A scaled-up prototype is designed, fabricated and tested through the experiment to verify the structure design of the microgripper.